SYSTEMATIC LITERATURE REVIEW: THE EXISTENCE OF FLEXING CULTURE AS A LIFESTYLE FOR TODAY'S INDONESIAN GENERATION Z - Firstiyanti, Aulia (Jurnal Sosial Humaniora dan Pendidikan, 2023)
We live in a world where status is determined by wearing a logo, driving a sports car, listening with AirPods. The aim of this research is to answer the role of social media in social culture, especially the flexing culture phenomenon. This research applies the Systematic Literature Review method. Based on the results of a systematic literature review, within two weeks the researcher found 10 journals related to the culture of showing off wealth (flexing culture) and took three of them which according to the author were in accordance with what the author wanted to find. The researcher used the GARUDA portal and Google Scholar as tools. in searching for these journals. The findings show that social media can influence a netizen's lifestyle. Either from the way of thinking or behaving.